Estimation of finite population variance using auxiliary information in sample surveys - Housila P. Singh; Alok K. Singh; Ramkrishna S. Solanki (Statistica, 2014)
This paper addresses the problem of estimating the finite population variance using auxiliary information in sample surveys. Motivated by (Singh and Vishwakarma, 2009) some estimators of finite population variance have been suggested along with their properties in simple random sampling. The theoretical conditions under which the proposed estimators are more efficient than usual unbiased, usual ratio and (Singh et al., 2009) estimators have been obtained. Numerical illustrations are given in support of the present study.